The pyran ring isopentene group: an overlooked antimicrobial active group in prenylated flavonoids. Issue 22 (17th November 2022) - Pang, Daorui; Liao, Sentai; Zhou, Pengfei; Liu, Fan; Zou, Yuxiao
Abstract: Prenylated flavonoids show antibacterial activity towards Staphylococcus aureus ( S. aureus ). Previous studies have suggested that the prenyl side-chain is an important active group for antimicrobial activity. However, prenylated flavonoids also often contain a pyran ring isopentene group. Few studies have explored the contribution of the pyran ring isopentene group to antibacterial activity. In this study, the antibacterial activities of structurally related flavonoid compounds from mulberry root bark were studied by detecting the minimum inhibitory concentration (MIC) and colony counting. These flavonoid compounds all exhibited antibacterial activities against S. aureus ATCC6538, S. aureus ATCC25923 and methicillin-resistant S. aureus (MRSA) ATCC43300 with MIC values of 7.3–248.2 μmol/L, 7.3–330.9 μmol/L, and 7.3–330.9 μmol/L, respectively. Structure-activity relationship analyses demonstrated that the pyran ring isopentene group plays an important role in antibacterial activity. Thus, the pyran ring isopentene group is an overlooked antimicrobial active group in prenylated flavonoids. GRAPHICAL ABSTRACT: UF0001